Aplikasi Sistem Pakar Untuk Mengidentifikasi Biota Laut Berbasis Website - Medianti, Vebyola Dwi; Maulana, Iqbal (Jurnal Teknik Informatika UNIKA Santo Thomas, 2022)
Indonesia has very wide waters and has a diversity of marine ecosystems. This diversity makes people want to know information about various marine ecosystems and marine biota easily and quickly without having to buy or read books about marine ecosystems. Along with the development of technology and information in everyday life, it can be used to solve these problems by designing an expert system that can contain various information to identify various types of marine biota. To design the expert system, it takes several stages such as needs analysis, knowledge acquisition, system design, coding, and testing the system. In this research, applying the knowledge base of rule based relation with the knowledge representation of decision tree. The marine biota expert system is designed based on a website. This expert system produces an accuracy of 100%